High fat diet causes distinct aberrations in the testicular proteome - Jarvis, S. (Int J Obes (Lond), 2020)
Diet has important effects on normal physiology and the potential deleterious effects of high fat diets and obesity on male reproductive health are being increasingly described. We conducted a histological review of the effects of chronic high fat (HF) diet (using a mouse model fed a 45% fat diet for 21 weeks) with a discovery proteomic study to assess for changes in the abundance of proteins in the testis. Mice on a HF diet became obese and developed glucose intolerance. Using mass spectrometry, we identify 102 proteins affected in the testis of obese mice. These included structural proteins important for the blood testis barrier (filamin A, FLNA), proteins involved in oxidative stress responses (spermatogenesis associated 20, SPATA-20) and lipid homoeostasis (sterol regulatory element-binding protein 2, SREBP2 and apolipoprotein A1, APOA1). In addition, an important regulator protein paraspeckle component 1, PSPC-1, which interacts with the androgen receptor was significantly downregulated. Proteomic data was validated using both Western blotting and immunostaining which confirmed and localised protein expression in both mouse and human testis using biopsy specimens. This study focused mainly on the abnormalities that occurred at the protein level and as a result, we have identified several candidate proteins and conducted pathway analysis around the effects of HF diet on the testis providing novel insights not previously described. Some of the identified targets could be targeted therapeutically and future work is directed in this area.